الرهنان الحيازي والرسمي في النظام المالي الإسلامي الماليزي دراسة فقهية تحليلية = Possessory and official mortgages in Malaysian Islamic monetary system: a fiqh analytical study = Gadaian Hiyazi dan gadaian rasmi dalam sistem kewangan Islam Malaysia: satu kajian analisis fiqh - Zakariyah, Luqman; Amanullah, Muhammad; Musa, Mohammed Kabiru (IIUM Press, 2017)
This study aims to explain the possessory and official pledges and some of their applications in the Malaysia Islamic monetary system from the point of view of Fiqh analysis. This is to answer the question: what are the concepts of possessory and official mortgage and their applications? The study refers to the views of the jurists on the issue and compares between them. The study concludes among others: that the traditional jurists did not differentiate between the possessory and official mortgages in their discussions but rather discussed it in a general manner. Legal scholars had reviewed this form of interaction as a result of in the real estate insurance system; and that the difference between them is that possessory mortgage has the mortgaged property in the hand of the mortgagee until he fulfils his right and as for the official mortgage, the mortgagee remains in the hand of the owner and the mortgagee has the right in fulfilling his right based on the price of the mortgaged item. This mechanism however, was applied in different manners in the Malaysia Islamic monetary system; some of which comply with the Shari’ah while some others need to be reviewed and studied further to contain them from some of the Shari’ah offences and the possibility of them containing elements of the suspicious usury.